Exploration of the Path for Undergraduate Party Organizations to Carry out Party History Learning and Education - Yan, Gong (Journal of Theory and Practice of Social Science, 2024)
Looking back on the glorious hundred year history of the Party, the CPC has experienced painful hesitation and setbacks. Even so, the people of the CPC always adhere to the original intention and mission of seeking happiness for the Chinese people and rejuvenation of the Chinese nation. To showcase the light of the 72 years since the founding of the People's Republic of China To celebrate the 100th anniversary of the founding of the CPC, Party organizations in colleges and universities should be strong. Set political beliefs, enhance party spirit principles, adhere to the Party's original aspiration and mission, persist in providing education that satisfies the people, never forget the past, walk well in the present, and create the future. The author conducts a preliminary exploration and exploration of party history learning and education in higher education party organizations from the following aspects, based on the theme activities of party history learning and education carried out by the school.